SCALE FOR ASSESSING INDIVIDUAL RISK OF BARIATRIC SURGERY - Khamdamov I. B. (Web of Journals Publishing, 2024)
Thus, the developed “Scale for assessing the individual risk of bariatric surgery” has sufficient sensitivity and specificity to predict any complications, and can be used in clinical practice to predict and manage the risks of this type of surgical intervention.
Keywords: gastric bypass, longitudinal resection of the stomach in combination with small intestinal bypass.